B7 Family Members in Lymphoma: Promising Novel Targets for Tumor Immunotherapy? - Zhang, Wei; Qiu, Yu; Xie, Xiaoli; Fu, Yao; Wang, Lijuan; Cai, Zhen (Frontiers in Oncology, 2021)
T cells play a vital role in the immune responses against tumors. Costimulatory or coinhibitory molecules regulate T cell activation. Immune checkpoint inhibitors, such as programmed cell death protein 1 (PD-1) and programmed death ligand 1 (PD-L1) have shown remarkable benefits in patients with various tumor, but few patients have displayed significant immune responses against tumors after PD-1/PD-L1 immunotherapy and many have been completely unresponsive. Thus, researchers must explore novel immune checkpoints that trigger durable antitumor responses and improve clinical outcomes. In this regard, other B7 family checkpoint molecules have been identified, namely PD-L2, B7-H2, B7-H3, B7-H4 and B7-H6. The aim of the present article was to address the expression, clinical significance and roles of B7 family molecules in lymphoma, as well as in T and NK cell-mediated tumor immunity. B7 family checkpoints may offer novel and immunotherapeutic strategies for patients with lymphoma.